Registraion of Malaysian names using the atlas software - Kuak, M.S.J. (University of Malaya Library, 1992)
The Circle Module of the ATLAS Software is generally good but posed some problems with regards to the registration of Malaysian names. The limitation of the software is centered on the fact that it cannot accomodate Indian and Malay names, which have no surnames and Chinese names where the surnames occur before the personal names. The circulation division of the University of Malaya Library (UML) proposed 2 alternatives to solve the problem of the registratio of Malaysian names. Both solutions are satisfactory unless some customization is made on the software.